Cleansing efficacy of waist‐shaped inter‐dental brushes. A randomized‐controlled crossover study. (3rd November 2019) - Schnabl, Dagmar; Goebel, Georg; Kadletz, Alice; Gaenzer, Hanna; Steiner, René; Laimer, Johannes; Kapferer‐Seebacher, Ines
Abstract: Objective: To compare the cleansing efficacy of waist‐shaped versus cylindric inter‐dental brushes in patients receiving supportive periodontal therapy. Materials and methods: After sample size estimation, 20 periodontal maintenance patients diagnosed with periodontitis stage 3 were recruited. Brushing efficacy of waist‐shaped and cylindric inter‐dental brushes was evaluated in a randomized‐controlled, examiner‐blinded, two‐period crossover study by assessment of the Turesky modification of Quigley‐Hein plaque index (T‐QHI) and the papillary bleeding index (PBI) at four sites per tooth. Results: Seventeen probands with 1, 474 tooth sites finished the study. At baseline, median of overall T‐QHI scores was 1.4 (interquartile range 1.38–1.92). After 1 month, T‐QHI for waist‐shaped inter‐dental brushes was 1.24 (1.03–1.52); in 15 individuals, T‐QHI 0 was the grade most often measured. T‐QHI for cylindric brushes was 1.71 (1.18–2.29; p  = .042), with T‐QHI 0 being the grade most often measured only in seven individuals. The odds ratio for establishing plaque‐free inter‐dental sites with waist‐shaped relative to cylindric brushes was 1.8 [95% CI 1.6–1.9] ( p  < .001; logistic regression analysis). There were no statistically significant differences between PBI levels of waist‐shaped and cylindric brushes. Conclusion: This study has demonstrated the superiority in cleansing efficacy of waist‐shaped over cylindric inter‐dental brushes in individuals receiving supportive periodontal treatment.